Therapeutic Response and Possible Biomarkers in Acute Attacks of Neuromyelitis Optica Spectrum Disorders: A Prospective Observational Study - Wang, Jingqi; Cui, Chunping; Lu, Yaxin; Chang, Yanyu; Wang, Yuge; Li, Rui; Shan, Yilong; Sun, Xiaobo; Long, Youming; Wang, Honghao; Wang, Zhanhang; Lee, Michael; et al. (Frontiers in Immunology, 2021)
Objective: To explore the outcomes of NMOSD attacks and investigate serum biomarkers for prognosis and severity. Method: Patients with NMOSD attacks were prospectively and observationally enrolled from January 2019 to December 2020 at four hospitals in Guangzhou, southern China. Data were collected at attack, discharge and 1/3/6 months after acute treatment. Serum cytokine/chemokine and neurofilament light chain (NfL) levels were examined at the onset stage. Results: One hundred patients with NMOSD attacks were included. The treatment comprised intravenous methylprednisolone pulse therapy alone (IVMP, 71%), IVMP combined with apheresis (8%), IVMP combined with intravenous immunoglobulin (18%) and other therapies(3%). EDSS scores decreased significantly from a medium of 4 (interquartile range 3.0–5.5) at attack to 3.5 (3.0–4.5) at discharge, 3.5 (2.0–4.0) at the 1-month visit and 3.0 (2.0–4.0) at the 3-month visit (p<0.01 in all comparisons). The remission rate was 38.0% at discharge and 63.3% at the 1-month visit. Notably, relapse occurred in 12.2% of 74 patients by the 6-month follow-up. Higher levels of T helper cell 2 (Th2)-related cytokines, including interleukin (IL)-4, IL-10, IL-13, and IL-1 receptor antagonist, predicted remission at the 1-month visit (OR=9.33, p=0.04). Serum NfL levels correlated positively with onset EDSS scores in acute-phase NMOSD (p<0.001, R2=0.487). Conclusions: Outcomes of NMOSD attacks were generally moderate. A high level of serum Th2-related cytokines predicted remission at the 1-month visit, and serum NfL may serve as a biomarker of disease severity at attack. Identifier: NCT04101058; URL: https://clinicaltrials.gov/ct2/show/NCT04101058.